Postoperative Nausea and Vomiting in Cancer Surgery: Present Views on the Solution of the Old Problem - D. S. Baskakov; V. E. Khoronenko (Общая реаниматология)
Postoperative nausea and vomiting (PONV) is one of the most common and unpleasant complications after surgery. It is distressing for patients, results in increased treatment costs, and may cause very serious complications in the early postoperative period. The incidence of PONV in different surgical fields varies with the pattern of a surgical intervention, by assuming particular importance in cancer surgical practice where the likelihood of its development is very high for a number of reasons. A large number of studies currently deal with the development of PONV prevention schemes. Major risk factors have been identified; there are novel recommendations on anesthetic maintenance from the antiemetogenic point of view; however, the described procedures are not yet able to fully get rid of a patient’s risk for developing a complication. Drugs from a group of serotonin 5HT3-receptor antagonists and metoclopramide hydrochloride in combinations with glu-cocorticosteroids and butyrophenones are most frequently included into PONV prevention regimens. There are more and more data on the antiemetogenic activity of ^-adrenoblockers and fl^-adrenoceptor agonists and on the possibilities of using them during anesthesia. In this review, we attempted to summarize today’s accumulated knowledge about risk factors and procedures for preventing PONV and to define some new and promising areas in its prevention after cancer surgery.